Inverse Function In Exercise,analytically show that the functions are inverse functions.Then use the graphing utility to show this graphically.
f(x) = e^2x-1
g(x) = 1/2 + In(x)1/2

Respuesta :

Answer:

[tex]f^{-1}(x)=g(x)=\frac{\text{ln}(x)}{2}+\frac{1}{2}[/tex]  

Step-by-step explanation:

Please find the attachment.

We have been given two functions as [tex](x)=e^{2x-1}[/tex] and [tex]g(x)=\frac{1}{2}+\frac{\text{ln}(x)}{2}[/tex]. We are asked to show that both functions are inverse of each other algebraically and graphically.

Let us find inverse function of [tex]f(x)=e^{2x-1}[/tex] as:

[tex]y=e^{2x-1}[/tex]

Interchange x and y values:  

[tex]x=e^{2y-1}[/tex]

Take natural log of both sides:

[tex]\text{ln}(x)=\text{ln}(e^{2y-1})[/tex]  

[tex]\text{ln}(x)=(2y-1)*\text{ln}(e)[/tex]  

[tex]\text{ln}(x)=(2y-1)*1[/tex]  

[tex]\text{ln}(x)=2y-1[/tex]  

[tex]\text{ln}(x)+1=2y-1+1[/tex]

[tex]\text{ln}(x)+1=2y[/tex]  

[tex]\frac{\text{ln}(x)+1}{2}=\frac{2y}{2}[/tex]  

[tex]\frac{\text{ln}(x)}{2}+\frac{1}{2}=y[/tex]  

[tex]f^{-1}(x)=\frac{\text{ln}(x)}{2}+\frac{1}{2}[/tex]  

Therefore, we can see that function [tex]g(x)=\frac{1}{2}+\frac{\text{ln}(x)}{2}[/tex] is inverse of function [tex]f(x)=e^{2x-1}[/tex].

We can see that both functions are symmetric about line [tex]y=x[/tex], therefore, both functions are inverse of each other.  

Ver imagen ApusApus